2019
DOI: 10.3390/environments6040041
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Noise around Hospital Areas: A Case Study

Abstract: Due to the particular characteristics of hospitals, these buildings are highly sensitive to environmental noise. However, they are usually located close or within urban agglomerations. Hence, hospitals are, in many cases, exposed to high levels of environmental noise. A study of one of the main hospitals in the Extremadura region (Spain) is presented here to allow a global assessment of the acoustic impact of outdoor sound sources. Both long- and short-term measurements were carried out, and a software model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
0
8
0
8
Order By: Relevance
“…Montes-González, et.al (2019) reported that one of the main hospitals in the Extremadura region (Spain) is presented here to allow a global assessment of the acoustic impact of outdoor sound sources. Taking into account the results obtained, the noise impact on this hospital is primarily influenced by three sound sources: road traffic, cooling towers of the hospital and the emergency helicopter (18) . Fillary, et.al.…”
Section: Sources Of Sound Levels In Hospitalsmentioning
confidence: 99%
“…Montes-González, et.al (2019) reported that one of the main hospitals in the Extremadura region (Spain) is presented here to allow a global assessment of the acoustic impact of outdoor sound sources. Taking into account the results obtained, the noise impact on this hospital is primarily influenced by three sound sources: road traffic, cooling towers of the hospital and the emergency helicopter (18) . Fillary, et.al.…”
Section: Sources Of Sound Levels In Hospitalsmentioning
confidence: 99%
“…Health facilities such as hospitals are one of the most noise-sensitive areas in urban environment since it accommodates several patients including those with underlying health conditions such as cardiovascular, metabolic, and respiratory chronic diseases. This has led to the introduction of very stringent noise limits of 30 and 45 dBA by the World Health Organisation (WHO) and US Environmental Protection Agency (US EPA), respectively to help control noise levels in indoor hospital environments (Montes-González et al, 2019). An investigation conducted in an intensive care unit (ICU) rooms in Saudi Arabia revealed a slight increase in 12-hour average noise levels during the morning ( 64.1 dBA) compared to the night (62.48 dBA), these levels far exceeded both the WHO hospital limits and outdoor levels of 55 dBA (Alduais and Salama, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hospitais são locais destinados ao tratamento, descanso e recuperação dos pacientes (LOUPA, 2020), normalmente localizados nos centros das cidades por questões de logística e acesso da população. No entanto, esta localização estratégica é intensamente afetada pela poluição sonora ocasionada, principalmente, pelo tráfego de veículos (MONTES-GONZÁLEZ et al 2019).…”
Section: Introductionunclassified
“…Diversos estudos ao redor do mundo avaliaram o ruído gerado por veículos no entorno dos hospitais FERRAZ, 2014;RAVINDRA et al, 2016;MONTES-GONZÁLEZ et al 2019;ANDRADE et al, 2021a). Proposição de medidas mitigadoras deste tipo de poluição, de maneira geral, estão relacionadas a simulações em softwares de acústica, com implementação da redução na frota de veículos circulantes (total, pesados), substituição do tipo de asfalto e redução na velocidade dos veículos (FIEDLER; ZANNIN, 2015;MONTES-GONZÁLEZ et al 2019). Medidas efetivas para avaliação da redução na poluição sonora com comparações são difíceis de serem implantadas, pela complexidade de fatores envolvidos na dinâmica das cidades.…”
Section: Introductionunclassified